2018
DOI: 10.3390/molecules23123228
|View full text |Cite
|
Sign up to set email alerts
|

Design and Properties of Ligand-Conjugated Guanine Oligonucleotides for Recovery of Mutated G-Quadruplexes

Abstract: The formation of a guanine quadruplex DNA structure (G4) is known to repress the expression of certain cancer-related genes. Consequently, a mutated G4 sequence can affect quadruplex formation and induce cancer progression. In this study, we developed an oligonucleotide derivative consisting of a ligand-containing guanine tract that replaces the mutated G4 guanine tract at the promoter of the vascular endothelial growth factor (VEGF) gene. A ligand moiety consisting of three types of polyaromatic hydrocarbons,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…A number of G4 ligands, including porphyrin and phthalocyanine, that interact with G-tetrads through stacking interactions have been characterized. , Since the G-tetrad is a common feature of all G4 topologies, these ligands cannot be used to target a particular G4 conformation. Alternatively, specific small ligands that discriminate G4 topologies have been reported, which may have the capacity to interact directly with G4 loops and grooves. , Further, these ligands have been used for sequence- or topology-dependent G4 sensing via their fluorescence, suggesting the application in topology-dependent control of replication by G4 ligands. , Additionally, we have recently demonstrated the topology-control of human vascular endothelial growth factor ( VEGF ) G4. , We found that it contains an oxidized guanine in one G-tract, which forms an unstable hybrid G4, and the replication stall did not occur. The ligand-conjugated guanine tract could be replaced with a G-tract of the VEGF G4 due to the unstable hybrid G4, which would help in replication process recovery, and regenerated parallel G4 to recover the replication stall.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…A number of G4 ligands, including porphyrin and phthalocyanine, that interact with G-tetrads through stacking interactions have been characterized. , Since the G-tetrad is a common feature of all G4 topologies, these ligands cannot be used to target a particular G4 conformation. Alternatively, specific small ligands that discriminate G4 topologies have been reported, which may have the capacity to interact directly with G4 loops and grooves. , Further, these ligands have been used for sequence- or topology-dependent G4 sensing via their fluorescence, suggesting the application in topology-dependent control of replication by G4 ligands. , Additionally, we have recently demonstrated the topology-control of human vascular endothelial growth factor ( VEGF ) G4. , We found that it contains an oxidized guanine in one G-tract, which forms an unstable hybrid G4, and the replication stall did not occur. The ligand-conjugated guanine tract could be replaced with a G-tract of the VEGF G4 due to the unstable hybrid G4, which would help in replication process recovery, and regenerated parallel G4 to recover the replication stall.…”
Section: Introductionmentioning
confidence: 96%
“…23,24 Additionally, we have recently demonstrated the topology-control of human vascular endothelial growth factor (VEGF) G4. 25,26 We found that it contains an oxidized guanine in one G-tract, which forms an unstable hybrid G4, and the replication stall did not occur. The ligand-conjugated guanine tract could be replaced with a G-tract of the VEGF G4 due to the unstable hybrid G4, which would help in replication process recovery, and regenerated parallel G4 to recover the replication stall.…”
Section: ■ Introductionmentioning
confidence: 99%